2016
DOI: 10.1038/srep24284
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of physical exercise and education on age-related cortical thinning in cognitively normal individuals

Abstract: We investigated the association between self-reported physical exercise and cortical thickness in a large sample of cognitively normal individuals. We also determined whether a combination of physical exercise and education had more protective effects on age-related cortical thinning than either parameter alone. A total of 1,842 participants were included in this analysis. Physical exercise was assessed using a questionnaire regarding intensity, frequency, and duration. Cortical thickness was measured using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 52 publications
2
40
1
Order By: Relevance
“…These regional findings align with results of previous studies evaluating CRF and cortical thickness in patient populations (Alosco et al, 2013; Scheewe et al, 2013) and mild cognitive impairment (Reiter et al, 2015), as well as with a study relating cortical thickness and subjectively reported exercise duration in normal aging (Lee et al, 2016). Notably, associations between CRF and cortical thickness reliably appear within multimodal association regions across both healthy and abnormal aging studies, suggesting that higher order cortices may be most sensitive to variation in CRF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These regional findings align with results of previous studies evaluating CRF and cortical thickness in patient populations (Alosco et al, 2013; Scheewe et al, 2013) and mild cognitive impairment (Reiter et al, 2015), as well as with a study relating cortical thickness and subjectively reported exercise duration in normal aging (Lee et al, 2016). Notably, associations between CRF and cortical thickness reliably appear within multimodal association regions across both healthy and abnormal aging studies, suggesting that higher order cortices may be most sensitive to variation in CRF.…”
Section: Discussionsupporting
confidence: 90%
“…Studies of patient populations (mild cognitive impairment, heart failure, and schizophrenia) have demonstrated positive associations between cortical thickness and CRF (Alosco et al, 2013; Reiter et al, 2015; Scheewe et al, 2013), yet the association between CRF and cortical thickness in the context of healthy aging remains unknown. One recent study (Lee et al, 2016) demonstrated a positive relation between self-reported physical activity and cortical thickness in healthy older adults. However, given that subjective CRF measures do not align well with objectively quantified peak VO 2 (Tager et al, 1998), additional study is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The observed association between YoE and higher cortical thickness in medial prefrontal, ACC, and orbitofrontal cortices provides further converging evidence to other neuroimaging studies conducted within the CR model (Arenaza-Urquijo et al, 2013;Kim et al, 2015;Lee et al, 2016;Boller et al, 2017;Vaqué-Alcázar et al, 2017). The relevance of distinct frontal lobe areas as mediators of CR mechanisms is probably related to their key role in cognitive processes such as working memory (Owen et al, 2005;Barbey et al, 2011), cognitive conflict monitoring (Jahn et al, 2016), or decision-making (Shenhav et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…Neuroimaging studies of cognitively normal older individuals have revealed positive associations between CR proxies and measures of brain integrity (i.e., regional volumes or cortical thickness; for review, see Bartrés-Faz and Arenaza-Urquijo, 2011). These associations are primarily observed in limbic, paralimbic, and heteromodal cortical association areas, particularly within the prefrontal cortex, and have typically been interpreted as reflecting a higher capacity for plastic change, which may increase the adaptability of higher-educated individuals to age-or disease-related brain changes (Valenzuela et al, 2008;Foubert-Samier et al, 2012;Arenaza-Urquijo et al, 2013Lee et al, 2016;Vaqué-Alcázar et al, 2017). This interpretation is corroborated by functional imaging studies that have demonstrated differential patterns of brain activation in these latter regions that are suggestive of greater neural efficiency and capacity in highereducated individuals Solé-Padullés et al, 2009;Fernández-Cabello et al, 2016;Stern et al, 2018a) and may reflect greater capacity for plastic change associated to the CR concept (Bartrés-Faz and Arenaza-Urquijo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An increased cortical thickness (San et al, 2016) was found to be effective when both education and physical exercise were combined. Increased cortical thickness in prefrontal cortex, precuneus, left postcentral gyrus, inferior parietal region correlates with longer duration of exercise but not with the intensity of exercise.…”
Section: Feature Based Morphometrymentioning
confidence: 99%